Analysis of Immortalized Normal Cell Lines Used in the Characterization of Oral Cancer. (23rd August 2013) - Dickman, Christopher T.; Towle, Rebecca; Saini, Rajan; Garnis, Cathie
Abstract : Objectives: 1) Evaluate the molecular profiles of a panel of normal and dysplastic cell lines used in modeling oral cancer initiation and progression. 2) Determine how closely they resemble microdissected tissue of the same type. Methods: Primary cell lines OKP7, OKF4; Immortalized normal cell lines OKF4/TERT‐1, OKF4/E6E7, OKF6/TERT‐1, OKF6/TERT‐2, OKF6/E6E7, OKP7/bmi1/TERT; and dysplastic cell lines DOK and POE9n/TERT were analyzed for DNA copy number variation, mRNA, and miRNA expression. These data were compared to microdisected normal and dysplastic tissue using SMRT v.2 DNA microarrays, Agilent Human Gene Expression 44K microarrays, and Exiqon LNA RT miRNA PCR panels. Results: All but one of the immortalized cell lines contained major alterations in DNA copy number. Clustering analysis showed that mRNA and miRNA expression of the immortalized normal cell lines is distinct from normal tissue and is more similar to the primary and dysplastic cell lines, regardless of the tissues from which they derived, or if and how they have been immortalized. However the expression of tumor suppressors for example p53 was significantly lower in the immortalized cells (p=0.0021), regardless of immortalization method. Conclusions: This experiment provides valuable information for those wishing to use normal or dysplastic oral cell lines. One will need to keep in mind the genomic mutations and the altered expression inherent to these lines when applying the conclusions of studies done on these cell lines.